The concept of freedom and wild life in the works of Jack London and Normurod Norqobilov - Karimova, Munira Ahmadjanovna (The Lingua Spectrum, 2026)
This article explores the concept of freedom and wild life in the literary works of Jack London and Normurod Norqobilov. The study analyzes how both writers portray the relationship between humans, animals, and nature through artistic and philosophical perspectives. Jack London’s works mainly reflect the struggle for survival, the instinct of freedom, and the harsh realities of the natural world. His characters often demonstrate courage, independence, and adaptation to wilderness conditions. In contrast, Normurod Norqobilov depicts freedom and wild life through national values, emotional experiences, and the harmony between humans and nature. The article compares similarities and differences in the authors’ approaches, emphasizing the symbolic meaning of animals and wilderness in their narratives. The research also discusses how cultural background, social environment, and literary traditions influence the representation of freedom in English and Uzbek literature. Through comparative analysis, the article highlights universal human values connected with liberty, survival, and respect for nature.